Ramadan, Pandemic, and Consumer-Audience Behaviors - Setiawan, Wawan (Jobmark: Journal of Branding and Marketing Communication, 2021)
During Ramadan, in Indonesia (the country with the largest Muslim population in the world), brand communication and product marketing, both themed and related to Ramadan, are always rife. How do consumers and audiences react to it? This article uses a descriptive analysis approach to dissect the latest secondary data from trusted research institutions. Research shows that household cleaning product brands are the most popular among consumers. This fact is not surprising because this year's Ramadan, like the last two Ramadans, Indonesia is still in a pandemic, although not as bad as before. Interestingly, the data also shows the high purchase of iftar products by non-Muslim consumers. Indonesia is a Muslim-majority country with an excellent tolerant culture, allowing free interaction and consumption among consumers with different ethnic and religious backgrounds. Media content that is widely watched by consumer audiences and media consumption behavior has also shifted. This study is helpful for brand owners or managers as a reference for brand communication strategies and product marketing. It is also helpful for scholars to examine the unique behavior of consumers and audiences during Ramadan, which researchers still rarely touch.